Dysregulation of ferroptosis may involve in the development of non‐small‐cell lung cancer in Xuanwei area. Issue 6 (2nd February 2021) - Li, Guangjian; Yang, Jiapeng; Zhao, Guangqiang; Shen, Zhenghai; Yang, Kaiyun; Tian, Linwei; Zhou, Qinghua; Chen, Ying; Huang, Yunchao
Abstract: The Xuanwei area of Yunnan Province, China, is one of the regions suffering from the highest occurrence and mortality rate of lung cancer in the world. Local residents tend to use bituminous coal as domestic fuel, which causes serious indoor air pollution and is established as the main carcinogen. After the local government carried out furnace and stove reform work, lung cancer rate including incidence and mortality among residents remains high. We herein wonder if there are specific mechanisms at protein level for the development of non‐small‐cell lung cancer (NSCLC) in this area. We investigated the changes of protein profiling in tumour of the patients from Xuanwei area. Tandem mass tag (TMT) was employed to screen the differential proteins between carcinoma and para‐carcinoma tissues. We identified a total of 422 differentially expressed proteins, among which 162 proteins were significantly up‐regulated and 260 were downregulated compared to para‐carcinoma tissues. Many of the differentially expressed proteins were related to extracellular matrix (ECM)‐receptor interaction, focal adhesion, PI3K/AKT pathway and ferroptosis. Further experiments on the two differential proteins, thioredoxin 2 (TXN2) and haptoglobin (HP), showed that the change of their expressions could make the lung cancer cell lines more resistant to erastin or RSL‐induced ferroptosis in vitro, and promote the growth of tumour in nude mice. In conclusion, this study revealed that aberrant regulation of ferroptosis may involve in the development of lung cancer in Xuanwei area.